2018
DOI: 10.1002/hed.25182
|View full text |Cite
|
Sign up to set email alerts
|

Helical intensity‐modulated radiotherapy with concurrent chemotherapy for oropharyngeal squamous cell carcinoma: A prospective investigation of acute swallowing and toxicity patterns

Abstract: Results confirm that patients with oropharyngeal SCC undergoing helical IMRT with chemotherapy continue to experience incidences of acute toxicities comparable with other conformal techniques, and need supportive cares.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
(164 reference statements)
0
12
0
Order By: Relevance
“…Concomitant radiotherapy and chemotherapy was associated with worse scores on the functional limitation domain in the bivariate analysis, which reflects problems regarding taste and the pronunciation of words, but this association lost its significance after the adjusted analysis. In contrast, other researchers report that concomitant radiotherapy and chemotherapy increases both acute and late‐onset toxicity compared to radiotherapy alone and other methods, causing dysgeusia and exerting a negative impact on quality of life . Histological studies involving rats have demonstrated that radiotherapy of the head and neck causes harm to the taste buds, affecting the perception of bitter, salty and sour flavors .…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant radiotherapy and chemotherapy was associated with worse scores on the functional limitation domain in the bivariate analysis, which reflects problems regarding taste and the pronunciation of words, but this association lost its significance after the adjusted analysis. In contrast, other researchers report that concomitant radiotherapy and chemotherapy increases both acute and late‐onset toxicity compared to radiotherapy alone and other methods, causing dysgeusia and exerting a negative impact on quality of life . Histological studies involving rats have demonstrated that radiotherapy of the head and neck causes harm to the taste buds, affecting the perception of bitter, salty and sour flavors .…”
Section: Discussionmentioning
confidence: 99%
“…The extent to which patients experience dysphagia is largely dependent on the size and location of the tumor, the modality and intensity of the treatment, and the nature of any surgical reconstruction 2,3 . Dysphagia is known to occur in the acute phases of treatment and can often be attributed to radiation‐induced toxicities, such as xerostomia, mucositis, pain, and loss of taste and sensation 4,5 . Three months post treatment, many of these acute toxicities have largely resolved and some patients, over the subsequent months, slowly experience a return to their baseline swallow function 4 .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Dysphagia is known to occur in the acute phases of treatment and can often be attributed to radiation-induced toxicities, such as xerostomia, mucositis, pain, and loss of taste and sensation. 4,5 Three months post treatment, many of these acute toxicities have largely resolved and some patients, over the subsequent months, slowly experience a return to their baseline swallow function. 4 However, other patients may see little or no recovery in their swallow function, with a recent population-based study demonstrating that up to 45% of patients are impacted by chronic dysphagia 2 years post treatment, 6 while a recent longitudinal study showed that up to 50% of patients continued to experience dysphagia 3 years post treatment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As symptoms presented by HNC patients such as xerostomia, dysgeusia, dysphagia, mucositis, and thick saliva [36,37] can limit oral intake [22] and lead to changes in food consistency, our results for macronutrients were expected. A lower macronutrient intake is expected when patients opt for pasty, liquid, or mild food [9], impacting in particular fiber content.…”
Section: Discussionmentioning
confidence: 71%